Effects of pentosan polysulfate sodium on joint structure and function out to six months in naturally-occurring canine osteoarthritis - Catherine J. M. Stapledon; Ravi Krishnan; Rachel A. Peat; Christian Reiter; Marjorie E. Milne; Stewart D. Ryan; Sebastien H. Bauquier; Thierry Beths (PLoS ONE, 2026)
Objective To evaluate the durability of effect and disease modification potential of a six-week course of pentosan polysulfate sodium (PPS) therapy out to 26 weeks (six months) in companion dogs with naturally-occurring osteoarthritis. Design Twenty mixed-breed companion dogs were enrolled and randomized to receive either subcutaneous 3 mg/kg PPS injections (n = 14) or placebo (n = 6) once weekly for six weeks. Dogs underwent assessments for pain, functional gait analysis, MRI, and biomarker analysis at baseline and selected timepoints. Results PPS treatment was well tolerated throughout the study. At baseline, the PPS-treated group had higher pain with Helsinki Chronic Pain Index (HCPI) scores of 15.14 compared to 8.83 in placebo. PPS-treated dogs experienced sustained HCPI reductions compared to placebo at 26 weeks after adjusting for differences in baseline pain. The PPS-treated group experienced normalization of gait symmetry up to week 26, indicating a reduction in lameness and an improvement in overall function. Total cartilage volume increased at weeks 8 and 26 from baseline in the PPS-treated group compared to placebo, and OA disease progression biomarker changes (CTX-I, HA, and TIMP-1) were consistent with slowed cartilage degradation at weeks 8 and 26. Conclusions PPS-treated dogs experienced improvements in pain, joint function, and cartilage volume compared to placebo, supported by changes in biomarkers at weeks 8 and 26. The 26-week timepoint in this translational canine model provides insights into the potential disease-modifying mechanisms and durability of PPS in long-term treatment outcomes in humans with OA.